Comparison of Effect of Two Education Management and Traditional Education Methods on Academic Motivation of Medical Students - Zeinab Sadeghi; Ali Arab; Reza Mohtashami (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objective: Motivation and interest play a major role in the learning process, and the student's academic motivation depends on teaching style to some extent. In fact, a student-oriented and flexible learning method can increase the activities of learners. This study aimed to describe the effects of education management on the academic motivation of medical students in education management pattern, compared to the traditional method in the morning report topic. Materials and Methods: This quasi-experimental study had a pretest-posttest design and was conducted on 30 medical students of Baqiyatallah University of Medical Sciences, Tehran, Iran, randomly divided into two test and control groups. Data were collected using Harter's Holding School questionnaire. Data analysis was performed using descriptive (mean and standard deviation) and inferential (independent t-test and univariate intergroup covariance) statistics. Results: In this study, the mean and standard deviation of academic motivation in the two groups of education management and traditional method were 92.53±10.126 and 12.68±116.66, respectively. Comparison of d mean score of satisfaction of students in two groups and univariate intergroup covariance (F=6.816 and P=0.015) showed a significant difference between the satisfaction scores of students in the two research groups (ɑ<0.05). Conclusion: According to the results of the study, the academic motivation of medical students was higher with the education management method, compared to traditional education. The model of education management led to better education and increased the academic motivation of students in the field of medicine by increasing motivation and reinforcing participatory spirit in these individuals.